Electronic Commerce Success Model: A Search for Multiple Criteria - Achjari, Didi; Quaddus, Mohammed A. (Gadjah Mada International Journal of Business, 2004)
The current study attempts to develop and examine framework of e-commerce success. In order to obtain comprehensive and robust measures, the framework accomodates key factors that are identified in the literature concerning the success of electronic commerce. The structural model comprises of four exogenous variables (Internal Driver, Internal Impediment, External Driver and Exgternal Impediment) and one endogenous variable (Electornic Commerce Success) eith 24 observed variables. The study that was administered within large Australian companies using questionaire survey concluded that benefits for both internal organization and external parties from the use of e-commerce were the main factor tro predict perceived and/or expected success of electronic commerce.